Verbal and Non-Verbal Sign on Inflight E-Magazine Garuda Indonesia “Colours” - Ni Putu Chika Maho Dewi; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study focuses on semiotic analysis and explains the meanings expressed by both verbal and non-verbal sign in Garuda Indonesia's in-flight e-magazine "Colours”. A descriptive qualitative method was employed in the analysis of this study in order to provide meaningful and well-organised explanations of the problem. Two theories—one supported by the research—were used in the analysis of signifiers and signified signs in this study. The first theories is Saussure's (1983) theory. According to Barthes (1986), there are two theories: denotation and connotation. And the last supported theory by Wierzbicka (1996) is the is the theory of colour terms. The aim of this research is to explain the verbal and non-verbal signs contained in the magazine and also find out what meaning is contained in the data. Through the analysis, the researcher found there are 24 data points for verbal and non-verbal signs. Connotative and denotative meanings were present in both spoken and nonverbal sign. Non-verbal signs are made up of images and colours, whereas verbal signs explain the product. Studi ini berkaitan dengan analisis semiotik dan menjelaskan makna yang disampaikan oleh tanda-tanda verbal dan nonverbal yang ditemukan dalam e-magazine inflight “Colours” oleh Garuda Indonesia. Dalam menganalisis penelitian ini, metode yang digunakan adalah metode deskriptif kualitatif untuk melakukan deskripsi yang jelas dan terorganisir tentang masalah. Mengenai analisis, ada dua teori dan satu teori yang didukung yang diterapkan dalam penelitian ini, yaitu teori Saussure (1983) dalam menganalisis penanda dan tanda yang ditandai. Teori kedua adalah arti denotasi dan konotasi oleh Barthes. (1986). Dan teori terakhir yang didukung oleh Wierzbicka (1996) adalah teori istilah warna. Tujuan penelitian ini adalah untuk menjelaskan tanda-tanda verbal dan non-verbal yang terkandung dalam majalah dan juga mencari tahu makna apa yang terdapat dalam data. Melalui analisis, peneliti menemukan ada 28 titik data untuk tanda-tanda verbal dan nonverbal. Tanda-tanda verbal dan nonverbal memiliki makna konotatif dan denotatif, sedangkan tanda-tanda nonverbal terdiri dari gambar dan warna.